Voyages of discovery - Boyle, David (Thames & Hudson, 2011)
In the three decades between 1492 and 1522, European merchants and explorers progressed from relative ignorance about the shape of the globe to knowledge of an atlas that was almost complete. They did so in search of spices, gold, silver and slaves, but with rudimentary technology, huge courage and boundless confidence in themselves and their calculations. The exchange of flora, fauna, diet, disease and culture changed the world within a few generations. The final touches to the pattern of oceans and continents came 2.5 centuries later with the voyages of James Cook. Voyages to Africa, Asia, the Americas and the Pacific and the legacies of those journeys and encounters are here dramatically described
Includes bibliographical references (131-132) and index
Keywords: Voyages and travels; Explorers; Discoveries in geography; Entdeckungsreise; Weltreise